Low-temperature 1Н NМR spectroscopic study of hydration properties of a hybrid system based on nanosilica, DNA and doxorubicin in the presence of C60 fullerene - Turov, V.V.; Prylutskyy, Yu.I.; Ugnivenko, A.P.; Barvinchenko, V.N.; Krupskaya, T.V.; Tsierkezos, N.G.; Ritter, U. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The structure of hydrate cover layers of SiO2–DNA–Dox (where Dox: doxorubicin) and SiO2–DNA–Dox–C60 fullerene hybrids was studied by means of low-temperature 1H NMR spectroscopy in tetrachloromethane. Thehydration properties of SiO2–DNA–Dox nanomaterials combined with fullerenes and their derivatives are extremely important for their further use as therapeutics in cancer treatment and for safety reasons. The findings reveal that the hydration properties of the hybrids differ from those of the solid DNA particulates or SiO2–DNA systems due to the existence of different types of water clusters, namely the weakly- (WAW) and strongly-associated water (SAW) clusters. For SAW clusters the radial distributions as well as the distributions of change in Gibbs free energy due to adsorptive interactions at the surfaces of the investigated systems were obtained.